Understanding the Well Control Procedures for optimizing the Well Control System during Drilling - Sultan, Muhammad Arsalan; Ahmed, Mazhar; Ali, Muzamil; Babar, Gul Zaman (American Journal of Computing and Engineering, 2022)
Well control is an essential part of any drilling operation. Improper well control procedure may result in blowout, and blowouts must be controlled to ensure a smooth drilling operation. The majority of well control incidents occur as a result of a failure to understand the fundamental principles involved. As a result, proper training and understanding are required for a drilling engineer. Every company in the world provides drilling engineers with training and an overview of various well control operations. The goal of taking well control as an engineering project is to think about and visualize the significance of well control in any drilling job. The purpose of this paper was to understand of well control procedures as well as the selection of the most effective well control system. The concurrent technique should only be utilized in exceptional circumstances; in the majority of occasions, the driller method is employed. However, if a suitable casing shoe is available, Wait & Weight method should also be used.